Campaña de lanzamiento para la nueva tienda de suplementos deportivos Mutant Store - Chimoy More, Valeria Alejandra (2023)
The present project involves creating a launch campaign for Mutant Store, a sports supplements store set to commence operations in November 2023. The plan's primary goals are to secure a 20% market share in digital channels and a 2% market share in offline channels while positioning Mutant Store products as the prime choice for extreme muscle development through physical exercise known for their effectiveness, robustness, and high quality. To meet these objectives, an extensive study revealed our target audience comprises men who prioritize both their physical and mental well-being through a balanced diet and consistent physical activity. Based on these insights, we developed a Brandbook for the brand, enabling us to define the visual identity for the campaign's advertisements. Subsequently, we created a comprehensive media plan that encompasses digital channels, ATL, BTL, and public relations.